2021
DOI: 10.4067/s0718-58392021000100027
|View full text |Cite
|
Sign up to set email alerts
|

Soil attributes and microbial diversity on 28 years of continuous and interrupted for 12 months of pig slurry application

Abstract: The pig slurry (PS) application as an organic fertilizer in Brazilian soils occurs for many years and the effects of this application are known, but in this study our objective was to evaluate the microbiological attributes and microbial diversity of the soil after the interruption of the PS application. The PS rates were 0, 30 and 60 m 3 ha-1 yr-1 and in 2016 the plots were divided and the PS application was stopped in half of the plot, generating the factorial scheme 2 × 2, being two PS rates (30 and 60 m 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Wastes from pig production are usually stored in anaerobic ponds and used as an alternative soil fertilizer for agricultural crops and pastures [6][7][8][9][10], with similar results to commercial soluble chemical fertilizers [11,12]. Studies have shown increases in biomass production and quality, lower environmental impacts and production costs, and improvements in soil physical, chemical, and biological attributes [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Wastes from pig production are usually stored in anaerobic ponds and used as an alternative soil fertilizer for agricultural crops and pastures [6][7][8][9][10], with similar results to commercial soluble chemical fertilizers [11,12]. Studies have shown increases in biomass production and quality, lower environmental impacts and production costs, and improvements in soil physical, chemical, and biological attributes [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in soil chemical [24,25], physical [16,26,27], and biological [28][29][30] attributes have been found with application of PS, with positive effects on soil quality, and crop yields [10,31,32]. These benefits are mainly due to increases in organic matter contents, which favor soil aggregation and availability of nutrients to plants.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, pig manure is not the most common source of nitrogen; it contributes around 10% to total manure production, compared to cattle slurry which is around 44% [20]. Pig slurry enriches soils with nutrients (nitrogen and carbon supply) and promotes microbiological processes [21][22][23][24], consequently influencing CO 2 , N 2 O, and NH 3 emissions [25,26]. The nitrogen content of pig slurry not only ensures balanced crop production and yields but also is a danger for nitrogen losses such as NH 3 emissions and nitrate (NO 3 − ) leaching to the surface and groundwater reservoirs [27,28].…”
Section: Introductionmentioning
confidence: 99%